Efektivitas Minyak Cengkeh, Nimba dan Kemiri Sunan, serta Ekstrak Babadotan Terhadap Penyakit Karat Daun Kopi (Hemileia vastatrix) - Efi Taufiq; Gusti Indriati; Rita Harni; Dibyo Pranowo (Pusat Penelitian dan Pengembangan Perkebunan, 2021)
Leaf rust disease (Hemileia vastatrix) is commonly controlled using synthetic fungicides. Plant oils and extracts are expected to reduce the pathogen. The research aimed to determine the effectiveness of clove, Reutealis trisperma, and neem oils, and Ageratum conyzoides extract against H. vastatrix. The study was conducted in the laboratory and greenhouse of the Indonesian Industrial and Beverage Crops Research Institute and smallholder coffee plantation in Garut, West Java, from January to December 2018. The A. conyzoides were extracted in the laboratories. Plant oils and extract's effectiveness was tested in vitro against the germination of urediniospore and in a greenhouse to inhibit disease development. The in vitro experiment were evaluated the eight concentrations of extract and oil were: 0 (steril water), 250, 500, 1000, 1500, 3000, and 5000 ppm. Whereas, in the greenhouse experiments used three concentrations of 1000, 2500, and 5000 ppm of the extract and oil, and 2000 ppm of Mankozeb (positive control). The greenhouse test was carried out on Arabica coffee plants, completely randomized design and five replications. The number of spots, disease intensity, and plant growth were examined periodically. The results showed that all of the the extract and oil inhibited the urediniospores germination, and the most effective concentrations were 500 ppm, 3000 ppm, and 5000 ppm. A. conyzoides extract, and clove oil effectively suppressed the infection of H. vastatrix by 75.99% and 64.00%, respectively, and comparable to the synthetic fungicide (68.00%).